Multivariate granger causality and the dynamic relationship between health care spending, income and relative price of health care in Malaysia - Tang, C.F. (2011)
This study employs the Granger causality test within a multivariate cointegration and error-correction framework to investigate the relationship between health care spending, income and relative price in Malaysia. This study covers the annual sample from 1970 to 2009. The main findings of this study are that in the short-run there is uni-directional Granger causality running from relative price to health care spending, while relative price and income are bidirectional Granger causality in Malaysia. In the long-run health care spending and income are bi-directional Granger causality, while there is uni-directional Granger causality running from relative price to health care spending and income. In addition, we also extend the study to examine the dynamic interaction between the variables in the system through the forecast error variance decomposition and impulse response function analyses. In line with the finding of Granger causality, all the variables behaved endogenously in the long-run. Thus, the variables are Granger-causes each other in the long-run even though there might be deviations in the short-run.